2021
DOI: 10.1101/2021.04.20.21255780
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Frequency of neurological manifestations in COVID-19: a systematic review and meta-analysis of 350 studies

Abstract: SummaryObjectiveTo summarize the frequency of neurological manifestations reported in COVID-19 patients and investigate the association of these manifestations with disease severity and mortality.DesignSystematic review and meta-analysisEligibility criteriaStudies enrolling consecutive COVID-19 patients (probable or confirmed) presenting with neurological manifestations.Data sourcesPubMed, Medline, Cochrane library, clinicaltrials.gov and EMBASE from 31st December 2019 to 15th December 2020.Data extraction and… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 25 publications
0
5
0
1
Order By: Relevance
“…12 Other studies have found a similar association between neurological diagnosis and severity of COVID-19 infection, particularly amongst older adults over 60 years of age. 13 The relationship between COVID-19 severity and neurological manifestations is likely bidirectional, as severely ill patients seem to be more likely to develop neurological complications related to severe systemic illness effects and those predisposed with underlying neurological may be predisposed to more severe COVID-19 illness. Similar to other hospital-based populations, the most commonly identified neurological diagnoses included encephalopathy followed by ischemic stroke.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 Other studies have found a similar association between neurological diagnosis and severity of COVID-19 infection, particularly amongst older adults over 60 years of age. 13 The relationship between COVID-19 severity and neurological manifestations is likely bidirectional, as severely ill patients seem to be more likely to develop neurological complications related to severe systemic illness effects and those predisposed with underlying neurological may be predisposed to more severe COVID-19 illness. Similar to other hospital-based populations, the most commonly identified neurological diagnoses included encephalopathy followed by ischemic stroke.…”
Section: Discussionmentioning
confidence: 99%
“…4 Delirium is significantly more common in older people who have COVID-19, with data from a recent meta-analysis and systematic review demonstrating 1 in 3 hospitalized older patients with COVID-19 are affected (pooled prevalence 34%), compared with 5% in young adults aged 18-34 years and 12% for all ages. 13 Importantly, delirium in older hospitalized patients has previously been demonstrated to be an independent risk factor for mortality and cognitive impairment. 6 Unique to our cohort, we identified that approximately one-third of neurologic conditions, including encephalopathy, stroke, and new onset seizures, were diagnosed at the time of initial hospital presentation, emphasizing that neurologic conditions are commonly presenting features in the acute phase of COVID-19 infection and may mask systemic symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Pandemics could disrupt the labor pool, causing acute supply chain disruptions with severe effects such as to food security (Huff et al 2015 ). A pandemic causing neurological harm, such as in long COVID (Misra 2021 ), could result in the human population having insufficient cognitive fitness to maintain civilization. Furthermore, these sorts of effects could have occurred during pandemics earlier in human history without leaving a noticeable trace.…”
Section: The Natural Global Catastrophic Risksmentioning
confidence: 99%
“…There is growing evidence indicating that neurological manifestations occur in patients as sequelae of COVID-19 (Misra et al, 2021 ). Approximately one-third of positive patients develop neurological and neuropsychiatric symptoms (Rudroff et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%